What's In a game? A game-based approach to exploring 21st-century European identity and values. Issue 1 (1st January 2019) - Leith, Murray; Boyle, Liz; Sim, Duncan; van der Zwet, Arno; Scott, Graham; Jimoyiannis, Athanassios; Jandrić, Petar; Hauge, Jannicke Baalsrud; Sultana Tany, Nadera; Hummel, Hans
ABSTRACT: This article focuses on the early stages of an international project on gamifying national identity. It examines the production of the content required for developing a sophisticated and engaging approach to pedagogical innovation in education, through game-based learning. This will encourage individuals to think about both European and national identity, specifically within the context of the European Union (EU). At a time when the EU faces significant challenges, a better understanding and appreciation of the role of national and supra-national identity and belonging in Europe is clear. RU EU? – an Erasmus+ funded project – aims to develop an innovative online game to help students and others enhance their understanding of their own national and European identities and challenge attitudes and prejudices. The content development of the game has brought together experts with socio-political knowledge, pedagogical understanding and technical expertise. This article discusses the early stages in the content development process, during which we amassed material from literature reviews, academic interviews and student focus groups and surveys. We sought to ensure that the content of the game reflected the issues raised within the game development lifecycle and our article describes our engagement with this material and its integration into game content.